2016
DOI: 10.1155/2016/5249086
|View full text |Cite
|
Sign up to set email alerts
|

An Update of Microsomal Prostaglandin E Synthase‐1 and PGE2 Receptors in Cardiovascular Health and Diseases

Abstract: Nonsteroidal anti-inflammatory drugs (NSAIDs), especially cyclooxygenase-2 (COX-2) selective inhibitors, are among the most widely used drugs to treat pain and inflammation. However, clinical trials have revealed that these inhibitors predisposed patients to a significantly increased cardiovascular risk, consisting of thrombosis, hypertension, myocardial infarction, heart failure, and sudden cardiac death. Thus, microsomal prostaglandin E (PGE) synthase-1 (mPGES-1), the key terminal enzyme involved in the synt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 82 publications
1
24
0
Order By: Relevance
“…The lipid mediator has diverse functions, including cytoprotection in the gastrointestinal tract, modulation of the immune system, and induction of the febrile responses. Furthermore, in the vascular system, PGE 2 reduced smooth muscle tone and changed proliferation and inflammatory activity (20)(21)(22)(23). Here, we observed that HDACi reduced the vascular PGE 2 level in the carotid, which resulted in attenuated arachidonic acid-induced relaxation suggesting an attenuated conversion of arachidonic acid to the vasodilator, PGE 2 (12,14,15).…”
Section: Discussionmentioning
confidence: 64%
“…The lipid mediator has diverse functions, including cytoprotection in the gastrointestinal tract, modulation of the immune system, and induction of the febrile responses. Furthermore, in the vascular system, PGE 2 reduced smooth muscle tone and changed proliferation and inflammatory activity (20)(21)(22)(23). Here, we observed that HDACi reduced the vascular PGE 2 level in the carotid, which resulted in attenuated arachidonic acid-induced relaxation suggesting an attenuated conversion of arachidonic acid to the vasodilator, PGE 2 (12,14,15).…”
Section: Discussionmentioning
confidence: 64%
“…In our study, various pro-inflammatory cytokines are highly expressed in the vitreous of PDR patients, indicating that inflammation may play an essential role in PDR progression. PGE 2 , a naturally occurring prostaglandin, serves as a key regulator involved in the inflammatory process in the cardiovascular system [31]. Inflammation in vascular diseases involves infiltrating inflammatory cells, circulating cells, immune cells and constitutive cells of vascular tissues.…”
Section: Discussionmentioning
confidence: 99%
“…17‐pt‐PGE2 was purchased from Cayman chemical. PGE2, 2‐Acetylhydrazide‐10(11H)‐carboxylic acid, 8‐Chloro‐dibenz [b, f] oxazepine‐10(11H)‐carboxylic acid (SC19220), (4Z)‐7‐[(rel‐1S,2S,5R)‐5‐((1,1′‐Biphenyl‐4‐yl)methoxy)‐ ‐2‐(4‐morpholinyl)‐3‐oxocyclopentyl]‐4‐heptenoic acid hemicalcium salt (AH23848), (2E)‐N‐[(5‐bromo‐2‐methoxyphenyl)sulfonyl]‐3‐[2‐(2‐naphthalenylmethyl)phenyl]‐2‐propenamide (L‐798106), 6‐isopropoxy‐9‐xanthone‐2‐carboxylic acid (AH6809), Dibutyryl‐cAMP (Db‐cAMP), Rp‐cAMP (Rp‐Adenosine 3′,5′‐cyclic monophosphorothioate triethylammonium salt) and 2‐APB were purchased from Sigma‐Aldrich. N‐[(1R)‐1,2,3,4‐Tetrahydro‐1‐naphthalenyl]‐1H‐benzimidazol‐2‐amine hydrochloride (NS8593) was purchased from Tocris (Bristol, UK).…”
Section: Methodsmentioning
confidence: 99%
“…Prostaglandin E2 (PGE2), derived from arachidonic acid through the action of cyclooxygenase‐1/‐2 (COX‐1/‐2) and PGE2 synthase, is a potent endogenous lipid mediator . It is the most widely produced prostanoid in the human body .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation